Risk Managament and Student Enrolment : The Mediating Effect of Security Risk Management - Eniola, Anthony Abiodun; Kenzhin, Zhaxat; Sultanova, Menslu (Australian and International Journal of Rural Education, 2023)
This study sought to determine whether students’ perceptions of health, security, and environmental risks influence student enrolment at private universities in rural areas of Nigeria, as well as whether security risks mediate the correlations between the variables in the study. The research utilised multistage sampling approaches to ascertain and analyse scientific knowledge on the impact of the perceptions of the three risk management variables on students from three different universities situated in the north, central and southwest regions and across six academic branches of learning. To analyse the study, the generalised structured component analysis method was used. The findings reveal that perceptions about environmental and health risks are very important and vital for university enrolment as well as performance. Although security is crucial, the results show that enrolment performance is notably moderate. This study concludes that examining risk linkages and correlations is a critical consideration for ensuring the sustainability and development of Nigeria’s higher education sector, as well as its strategic management.